Expression of MEP Pathway Genes and Non-volatile Sequestration Are Associated with Circadian Rhythm of Dominant Terpenoids Emission in Osmanthus fragrans Lour. Flowers - Zheng, Riru; Liu, Cai; Wang, Yanli; Luo, Jing; Zeng, Xiangling; Ding, Haiqin; Xiao, Wei; Gan, Jianping; Wang, Caiyun (Frontiers in Plant Science, 2017)
Osmanthus fragrans Lour. is one of the top ten traditional ornamental flowers in China famous for its unique fragrance. Preliminary study proved that the terpenoids including ionone, linalool and ocimene and their derivatives are the dominant aroma-active compounds that contribute greatly to the scent bouquet. Pollination observation implies the emission of aromatic terpenoids may follow a circadian rhythm. In this study, we investigated the variation of volatile terpenoids and its potential regulators. The results showed that both volatile and non-volatile terpenoids presented circadian oscillation with high emission or accumulation during the day and low emission or accumulation during the night. The volatile terpenoids always increased to reach their maximum values at 12:00 h, while free and glycosylated compounds continued increasing throughout the day. The depletion of non-volatile pool might provide the substrates for volatile emission at 0:00-6:00, suggesting the sequestration of non-volatile compounds acted like a buffer regulating emission of terpenoids. Further detection of MEP pathway genes demonstrated that their expressions increased significantly in parallel with the evident increase of both volatile and non-volatile terpenoids during the day, indicating that the gene expressions were also closely associated with terpenoid formation. Thus, the expression of MEP pathway genes and internal sequestration both played crucial roles in modulating circadian rhythm of terpenoid emission in O. fragrans.